Сравнительный анализ точности линейного и нелинейного преобразования режимных параметров дизель-генератора в фазу топливоподачи - Борисенко, Анатолий Николаевич; Кубрик, Борис Иванович; Лавриненко, Ольга Валериевна; Сосина, Елена Владимировна (НТУ "ХПИ", 2011)
The methodical error of linear and nonlinear transformation of angular speed of billow and moment of loading in the corner of passing of serve of fuel dizel-generator (DG), arising up in transient behaviors of its work at the sharp changes of moment of loading on its billow and different handling and output signals of the control system of power-plant, is analysed in the article
Keywords: двигатели внутреннего сгорания; силовая установка; момент нагрузки